Effect of salinity of groundwater on the geotechnical properties of some Egyptian clay - Mahmoud M. Abu zeid; Ahmed K. Abd El-Aal (Egyptian Journal of Petroleum)
This study deals with the effect of salinity of groundwater on some properties of clayey soil. Properties obtained from tests carried out on samples mixed with water containing different salt contents are compared with those obtained from tests carried out on samples mixed with pure water (tap water). The tested samples were taken from the site of the Faculty of Engineering in Qena, South Valley University. Two sets of samples of the clay soil were tested. One was mixed with pure water (pure water clay soil) and the other was mixed with salty water added to it in ratios ranging from 20% to 80% (clay soil mixed with salt). The test results showed the effect of groundwater salinity on the tested samples. The plasticity index decreased from 26 for pure water clay soil to 24.96 for clay soil mixed with 80% salt. The coefficient of consolidation increased from 0.00196 for pure water clay soil to 0.002744 for clay soil mixed with 80% salt. The California bearing ratio increased from 9.75% for pure water clay soil to 10.15% for clay soil mixed with 80% salt. The optimum moisture content increased from 14.25% for pure water clay soil to 16.5% for clay soil mixed with 100% salt. Decrease in the maximum dry density is observed for clay soil mixed with salty when compared with pure water clay soil. A marked decrease was noticed for the value of the unconfined compressive strength. All the tests were carried out in the Soil Mechanics and Foundations Lab, Faculty of Engineering in Qena, South Valley University.